Thermal, Metabolic and Hygric Physiology of the Little Red Kaluata, Daskaluta Rosamondae (Dasyuromorphia: Dasyuridae) - Withers, Philip; Cooper, Christine (Allen Press, 2009)
The little red kaluta (Dasykaluta rosamondae) is a small, insectivorous–carnivorous dasyurid marsupial found in arid spinifex grasslands of northwestern Australia. Kalutas resemble other dasyurids in many aspects of their physiology. Body temperature (Tb; 33.5°C; 1.5°C lower than predicted), wet thermal conductance (1.6 J g−1 h−1 °C−1; 91% of predicted), and dry thermal conductance (1.22 J g−1 h−1 °C−1; 55% of predicted) are not significantly different from allometric predictions for marsupials in the thermoneutral zone (26–33°C). A significantly lower-than-expected basal metabolic rate (0.55 ml O2 g−1 h−1; 58% of allometric prediction) and evaporative water loss (1.11 mg g−1 h−1; 39% of predicted) can be attributed to the combined effect of low Tb and phylogeny. Physiological adaptation to aridity is further reflected by a substantially smaller body mass (35 g) than predicted by phylogeny (200 g), a thermolabile Tb and use of torpor, which confer significant energy and water savings, and a high point of relative water economy (16.1°C).